Water Scorpions, Water Stick-Insects Ranatra spp. (Insecta: Hemiptera: Nepidae) - Taryn Griffith; Jennifer Gillett-Kaufman (EDIS)
Commonly mistaken for other objects due to its appearance, hence the common name water stick-insect, this slender reddish-brown insect is commonly found in fresh or brackish water (a mix of salt and fresh water) (Anufriyeva et al. 2016). They are ambush predators and will spend most of its time in the water waiting for prey. They are limited to the length of their raptorial forearms in terms of catching prey. In the southeastern United States, these insects are commonly referred to as water scorpions.